Budget impact analysis of a Lifestyle-integrated Functional Exercise (LiFE) program for older people in Germany: a Markov model based on data from the LiFE-is-LiFE trial - Dams, Judith; Gottschalk, Sophie; Schwenk, Michael; Nerz, Corinna; Becker, Clemens; Klenk, Jochen; Jansen, Carl-Philipp; König, Hans-Helmut (BMC geriatrics, 2024)
Fall prevention is important for healthy ageing, but the economic impact of fall prevention are scarcely investigated. A recent cost-effectiveness analysis compared a group-delivered Lifestyle-integrated Functional Exercise Program (gLiFE) with an individually-delivered program (LiFE) in community-dwelling people (aged ≥ 70 years) at risk of falling. In addition, the current study aimed to analyze the budget impact of LiFE and gLiFE, compared with standard care in Germany.
Online veröffentlicht: 23. Februar 2024
Gesehen am 06.08.2024